Evaluación de la microflora intestinal de pollos broiler con la adicion de ajo (allium sativum) al 2% y 3% en el balanceado en Palama-Salcedo - Plasencia Santafé, Carla Sofía (2015)
The present investigation was carried out in the county of Cotopaxi, canton Salcedo, parish Mulliquindil Santa Ana, neighborhood Palama, the main objective of the investigation was to Evaluate the intestinal microflora of chickens Broiler with the addition of garlic (Allium sativum) to 2% and 3% in the one balanced in Palama-Salcedo, to determine the percentage of the bacterial load and for ende the parameters of the productive indicators in chickens Broiler, (I consummate of food, increment of weight, nutritious conversion and yield to the channel). The used methodology was experimental, with that of a design totally at random (DCA). 90 chickens were selected, without sexar of 1 day of age they were divided in 3 compartments, in groups of 30 animals the compartments were identified totally at random, according to the percentage of addition of corresponding garlic, identified as: T1 (witness), T2 (balanced more 2% of garlic) and T3 (balanced more 3% of garlic), the consumption of garlic was every day in the morning, during the 45 days where the experiment....